Trifluridine- and tipiracil-induced DPD inhibition mimicking DPD deficiency: a case report - Schmitt, Antonin; Bouillet, Baptiste; Royer, Bernard; Ghinringhelli, François (Frontiers in Oncology, 2025)
Fluoropyrimidines, including 5-fluorouracil (5-FU) and its derivatives, remain the standard first-line treatment for metastatic colorectal cancer (mCRC). In recent years, trifluridine/tipiracil (TAS-102), an orally administered combination drug, has become a common third-line therapy for mCRC and could increasingly be used as first-line treatment. We report, for the first time, the case of an mCRC patient presenting discrepancies in uracilemia between measurements taken during (43.0 µg/L) and outside trifluridine/tipiracil treatment (7.3 and 4.5 µg/L). This inconsistency could be attributed to the metabolism of trifluridine into 5-carboxyuracil (5-CU), which can interfere with dihydropyrimidine dehydrogenase (DPD) phenotyping and cause falsely elevated uracilemia. This can lead to unnecessary reduction in the dose of fluoropyrimidines. Clinicians should be aware of this potential interaction when performing DPD phenotyping in patients treated with trifluridine/tipiracil, ensuring that testing is performed either before the treatment begins or after it has finished, or when genotyping DPYD.